THE TASKS OF REVIEWING AND FINDING THE RIGHT ORGANIZATIONAL CHANGE THEORY - Abayomi Oluwatosin Alase (International Journal of Educational Leadership and Management, 2017)
Organizational change is probably the singular most important undertaken that many organizations wish they could do to affect their productivities/profitability performances.  This review paper will highlight some of the well-known theories and approaches to organizational change.  In the late 1990s and early 2000s, America had one of the best economies in decades and many of her citizens were able to benefit from it both financially and educationally; the economy (and educational aspirations) grew expeditiously and lifted millions of Americans out of poverty.  These economical and educational turnarounds were achieved due in part to innovative and transformational leaders who understand that in order for businesses to grow, organizational change has to be an integral part of the process.  However, the issue now is that there seems to be too many complex and confusing change theories that profess to have the remedies for ‘fixing’ the organizational problems.  Ideally, however, this review paper will try to highlight the essentials of the selected organizational change and leadership theories and simplify them by making them accessible and understandable.  Additionally, this review will try to ease some of the confusions of the theories and potentially help guide the change agents to the appropriate organizational change theories.